Properties of Jambi Tempoyak; The effects of salts concentration - Nizori, Addion; Mursalin, Mursalin (Department of Technology of Agricultural product (THP) Jambi University, 2017)
Abstract— Tempoyak was made from fermented durian flesh, which very popular among Jambi people Indonesia. This study aims to isolate and identification of bacteria developed during fermentations process, determine physical-chemical properties of tempoyak as the effect of adding salts at various concentration and the sensory evaluations of tempoyak produced is also evaluated. The predominants microorganisms present in tempoyak were Lactobacillus bacteria. The results also showed that the level of salts concentration has a significant effect on pH, lactic acid content, however, has not significant impact on sensory evaluations. The best results was 3% of adding salts with the product properties of pH 3.64, lactic acid content 3.11% and overall acceptance score is 3.41. Keywords— Tempoyak, fermented foods, salts and sensory